1999
DOI: 10.1117/12.336943
|View full text |Cite
|
Sign up to set email alerts
|

Computer simulation of gene detection without PCR by single molecule detection

Abstract: Pioneer Hi-Bred is developing a low-cost method for rapid screening of DNA, for use in research on elite crop seed genetics. Unamplified genomic DNA with the requisite base sequence is simultaneously labeled by two different colored fluorescent probes, which hybridize near the selected gene. Dual-channel single molecule detection (SMD) within a flow cell then provides a sensitive and specific assay for the gene. The technique has been demonstrated using frequency-doubled Nd:YAG laser excitation of two visible-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Figure 11 illustrates a simple algorithm by which the ACF may be accumulated in real time as a histogram of cumulative delay times [11], obviating the need for a hardware correlator. Reference [12] includes an algorithm for accumulation of cross-correlation functions (CCFs). Figure 11 also illustrates the accumulation of a family of histograms of delay times between successive numbers of photons (SPIDA) [10].…”
Section: Data Reduction Methodsmentioning
confidence: 99%
“…Figure 11 illustrates a simple algorithm by which the ACF may be accumulated in real time as a histogram of cumulative delay times [11], obviating the need for a hardware correlator. Reference [12] includes an algorithm for accumulation of cross-correlation functions (CCFs). Figure 11 also illustrates the accumulation of a family of histograms of delay times between successive numbers of photons (SPIDA) [10].…”
Section: Data Reduction Methodsmentioning
confidence: 99%
“…The use of Monte Carlo simulations for validating experiments and determining feasibility limits was described in the first reports on the detection of single-chromophore molecules in solution [2]. Later simulations have been used to study efficiency of detection [20], two-color coincidence detection limits [21], and the efficiency of neural network analysis for distinguishing single molecules with different spectroscopic properties [22]. Section 2 presents an overview of the experiments and results.…”
Section: Introductionmentioning
confidence: 99%
“…Details and key sections of the computer code for these evaluations can be found in Ref. 1. The WSS is evaluated using the Gaussian weighting function that corresponds to the mean fluorescence signal expected from a fluorophore that passes in a straight line through the center of the probe region, without photodegradation or intersystem crossing.…”
Section: Monte Carlo Simulationmentioning
confidence: 99%
“…1 For example, for 'conventional' DNA sequencing by the Sanger method, the electrophoresis within a capillary or slab gel may be multiplexed by the use of spectroscopically identifiable fluorescent labels. Lieberwirth et al 2 have recently demonstrated such multiplex dye DNA sequencing in capillary gel electrophoresis by the use of four dyes with disparate fluorescence lifetimes.…”
Section: Intr0:ducti0nmentioning
confidence: 99%